A Case Study in Astronomical 3D Printing: The Mysterious η Carinae. (17th April 2017) - Madura, Thomas I.
Abstract: Three-dimensional (3D) printing moves beyond interactive 3D graphics and provides an excellent tool for both visual and tactile learners, since 3D printing can now easily communicate complex geometries and full color information. Some limitations of interactive 3D graphics are also alleviated by 3D printable models, including issues of limited software support, portability, accessibility, and sustainability. We describe the motivations, methods, and results of our work on using 3D printing (1) to visualize and understand the η Car Homunculus nebula and central binary system and (2) for astronomy outreach and education, specifically, with visually impaired students. One new result we present is the ability to 3D print full-color models of η Car's colliding stellar winds. We also demonstrate how 3D printing has helped us communicate our improved understanding of the detailed structure of η Car's Homunculus nebula and central binary colliding stellar winds, and their links to each other. Attached to this article are full-color 3D printable files of both a red-blue Homunculus model and the η Car colliding stellar winds at orbital phase 1.045. 3D printing could prove to be vital to how astronomer's reach out and share their work with each other, the public, and new audiences.